2008
DOI: 10.1080/13561820802190483
|View full text |Cite
|
Sign up to set email alerts
|

From students to professionals: Results of a longitudinal study of attitudes to pre-qualifying collaborative learning and working in health and social care in the United Kingdom

Abstract: During a longitudinal evaluation of a pre-qualifying interprofessional curriculum, health and social care students completed questionnaires concerning communication and teamwork skills and interprofessional learning and working. Data were collected on entry to their educational programme, during the second year of study, at qualification and after 9-12 months' qualified practice. This paper presents results from practice data from 414 professionals; 275 were educated on the interprofessional curriculum, 139 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 31 publications
4
75
0
4
Order By: Relevance
“…Although some studies demonstrated sustained attitude change over a few months to almost two years as a result of an intervention (Bajnok, Puddester, MacDonald, Archibald, & Kuhl, 2012;Pollard & Miers, 2008), this study provided preliminary evidence that no change in attitude toward interprofessional healthcare teams and perception of teamwork skill proficiency resulted from an interprofessional clinical education intervention program for osteopathic physicians seven to11 years post-medical school. Interprofessional clinical education programs seem to improve teamwork knowledge and skills for medical students (Reeves, Goldman, Burton, & Sawatzky-Girling, 2010; but may not have long-lasting effects for them as seasoned medical professionals.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although some studies demonstrated sustained attitude change over a few months to almost two years as a result of an intervention (Bajnok, Puddester, MacDonald, Archibald, & Kuhl, 2012;Pollard & Miers, 2008), this study provided preliminary evidence that no change in attitude toward interprofessional healthcare teams and perception of teamwork skill proficiency resulted from an interprofessional clinical education intervention program for osteopathic physicians seven to11 years post-medical school. Interprofessional clinical education programs seem to improve teamwork knowledge and skills for medical students (Reeves, Goldman, Burton, & Sawatzky-Girling, 2010; but may not have long-lasting effects for them as seasoned medical professionals.…”
Section: Discussionmentioning
confidence: 92%
“…Documentation of long-term impact of interprofessional education on medical practice is limited, although in some cases, attitudinal changes were sustained three months (Bajnok, Puddester, MacDonald, Archibald, & Kuhl, 2012) to one to two years beyond intervention (Pollard & Miers, 2008). Without continuing education, managerial follow-up, and reinforcement, though, this type of change is less likely to be sustained (Henderson, 2012).…”
Section: Implications For Interprofessional Practicementioning
confidence: 99%
“…The results of research studies into the effectiveness of IPE in achieving the desired outcome were inconclusive. However, the recent longitudinal study of pre-qualifying health and social care students by Pollard and Miers (2008) has been more promising. The benefits of interprofessional education were evident about 12 months into practice with professionals demonstrating more confidence in their own skills and the relationships established with other professionals.…”
Section: Pedagogical Challenges Of Experiential or Applied Learningmentioning
confidence: 99%
“…These range from students holding more positive views about working interprofessionally at the beginning of such programs than when they finished (Mandy et al, 2004;Pollard et al, 2006), to those where students articulated more positive responses at its conclusion (Pollard & Miers, 2008;Smith & Anderson, 2007). Differences between expectations and the realities of experience were evident in most studies.…”
Section: Pedagogical Challenges Of Experiential or Applied Learningmentioning
confidence: 99%
See 1 more Smart Citation